Risk Assessment of Low-Speed Wind Power Projects Based on an Aggregated Cloud Method: A Case in China. (23rd September 2018) - Wu, Yunna; Ji, Shaoyu; Wang, Jing; Song, Zixin
Abstract : Due to the aggravating wind curtailment phenomenon, low-speed wind power project (LSWPP) with the superiority of its generation being absorbed locally is rapidly developing in China. As the risk and opportunity coexist, a comprehensive risk assessment should be implemented to evaluate the risk level of a LSWPP. This paper firstly identified 38 risk factors based on a questionnaire survey and then sorted out 17 critical risk factors and divided them into 4 criteria to form the evaluation index system. In order to overcome the deficiencies of not considering randomness of linguistic variables and neglecting the interrelationship between factors, we proposed an aggregated method which combined ANP, the cloud theory, and the technique for order preference by similarity to ideal solution (TOPSIS) for LSWPPs risk assessment. After a case in China was studied and the sensitivity was tested, the effectiveness and application of this framework are demonstrated. Through the calculation of membership of each project, it indicated that the overall risk level of LSWPPs is relatively high. Finally, some recommendations of each critical risk factor were given for government, investors, and decision-makers to help them make more appropriate decisions and distribute the limited resources more rationally.